Inverse association between isoflavones and prediabetes risk: evidence from NHANES 2007–2010 and 2017–2018 - Zhou, Yanjun; Qin, Shaolei; Zhu, Yan; Xu, Peng; Gu, Ke (Frontiers in Nutrition, 2023)
Prediabetes is a metabolic condition characterized by blood glucose levels that are higher than normal but do not meet the threshold for a diabetes diagnosis. Individuals with prediabetes are at an increased risk of developing type 2 diabetes and associated complications. However, limited epidemiological studies have investigated the association between flavonoids from plant-based diets and the risk of prediabetes, and the existing evidence from these studies is inconsistent. Therefore, our study aimed to address this research gap by conducting a robust investigation into the potential association between flavonoid intake and prediabetes risk. To further confirm the inverse association between isoflavones and prediabetes risk, we also analyzed the correlation between concentrations of isoflavones and their metabolites in urine and prediabetes risk. We utilized data from 19,021 participants (mean age: 32.03 years) in the National Health and Nutrition Examination Survey (NHANES) conducted during 2007-2010 and 2017-2018. Our findings revealed an inverse association between the intake of glycitein (OR: 0.88; 95% CI: 0.82-0.96; p = 0.003), genistein (OR: 0.98; 95% CI: 0.97-0.99; p = 0.004), daidzein (OR: 0.98; 95% CI: 0.96-0.99; p = 0.009), and total isoflavones (OR: 0.99; 95% CI: 0.98-1.00; p = 0.005) with the risk of prediabetes based on weighted logistic regression analysis. Moreover, in a separate analysis of 3,706 participants (mean age: 35.98 years) from NHANES 2007-2010, we observed an inverse association between the concentration of daidzein in urine (OR: 0.84; 95% CI: 0.73-0.96; p = 0.012) and the concentration of genistein in urine genistein (OR:0.83; 95% CI: 0.75-0.93; p = 0.003) with the risk of prediabetes using weighted logistic regression. In conclusion, our findings suggest a potential protective effect of isoflavones against the development of prediabetes.